Rapid Flash-Paper Combustion Synthesis of Technological Metals (Ag, Cu, Ni, Co) - Athanasios B. Bourlinos; Dimitrios Moschovas; Apostolos Avgeropoulos; Theofanis N. Maimaris; Constantinos E. Salmas; Michael A. Karakassides (Sustainable Chemical Engineering, 2026)
A rapid, low-cost, and scalable flash-paper combustion method is presented for the synthesis of technologically important conductive (Ag, Cu) and magnetic (Ni, Co) metals. In this approach, nitrocellulose-based flash paper functions simultaneously as a fuel and an in situ reducing agent, enabling a self-sustained, highly exothermic reaction to take place. Metal salt-impregnated sheets, prepared from aqueous solutions, are simply dried and ignited, resulting in the rapid formation of metallic powders within seconds, without the need for external reducing agents or prolonged thermal processing. The resulting products were characterized using X-Ray Diffraction (XRD), confirming the formation of crystalline metallic phases, while electron microscopy revealed the formation of coarse, globular particles (30-90 μm) exhibiting compact morphology and low surface area (< 10 m2·g-1). Phase analysis further indicated high metal purity (> 90%) for Ag, Cu, and Ni, whereas Co exhibited comparatively lower purity due to its higher susceptibility to oxidation during combustion. Functional validation was achieved by demonstrating electrical conductivity (Ag, Cu) through simple paper-based circuits and magnetic behavior (Ni, Co) via magnetization measurements. In addition, the intense heat generated during combustion was explored for proof-of-concept thermal and thermophotovoltaic energy harvesting. Compared to conventional metallurgical and chemical reduction routes, this method offers a unique combination of operational simplicity, ultrafast processing, reduced energy input, and elimination of costly chemical reductants. These features position flash-paper combustion as a promising platform for scalable production of functional metals, particularly in decentralized or resource-limited settings.